Can Relaxing Make You Cognitively Faster - Lopamudra Naik (Current Progress in Medicine and Medical Research Vol. 6, 2023)
The aim of this chapter was to examine the effect of Yoga based relaxation technique on auditory and visual reaction time. This study adopted a two groups pre-post design. A total of 115 students were assessed for auditory and visual reaction time pre and post performing a Yogic relaxation technique using simple reaction time task in inquisit software (version 4.0.10.0).Data was analysed using JASP software. The study indicated that there was a significant decrease in auditory and visual reaction time post performing yogic Deep Relaxation Technique showing that s that DRT helps to increase the awareness and attention of individuals.